The Role of Adiponectin in the Pathogenesis of Metabolic Disturbances in Patients With Schizophrenia - Chen, Cynthia Yi-An; Goh, Kah Kheng; Chen, Chun-Hsin; Lu, Mong-Liang (Frontiers in Psychiatry, 2021)
Antipsychotic-induced metabolic disturbance is a common adverse event occurring in patients treated with antipsychotic drugs. The mechanisms underlying metabolic dysregulation are complex, involving various neurochemical and hormonal systems, interaction of genetic and lifestyle risk factors, and the antipsychotic drug prescribed. Recently, an increasing interest exists on the relation between antipsychotic-induced metabolic disturbances and body weight regulatory hormones such as adiponectin. Adiponectin is an adipose-derived protein related to insulin sensitivity, weight gain, and anti-inflammation, which has attracted great attention due to its potential role of being a biomarker to predict cardiovascular and metabolic diseases. Previous reports have suggested controversial results of the effects of antipsychotics on blood adiponectin levels. Several factors might contribute to those inconsistent results, including different antipsychotic drugs, duration of patients’ antipsychotic exposure, age, sex, and ethnicity. Here we summarize the existing evidence on the link between blood adiponectin levels and metabolic disturbances related to antipsychotic drugs in patients with schizophrenia. We further discuss the effects of individual antipsychotics, patients’ gender, ethnicity, age, and treatment duration on those relationships. We propose that olanzapine and clozapine might have the time-dependent biphasic effect on blood adiponectin levels in patients with schizophrenia.